2022
DOI: 10.1002/anie.202212335
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Modulation of Electrocatalytic Oxygen Reduction Activities of Single‐Atom Catalysts throughp‐nJunction Rectification

Abstract: Fine-tuning single-atom catalysts (SACs) to surpass their activity limit remains challenging at their atomic scale. Herein, we exploit p-type semiconducting character of SACs having a metal center coordinated to nitrogen donors (MeN x ) and rectify their local charge density by an n-type semiconductor support. With iron phthalocyanine (FePc) as a model SAC, introducing an n-type gallium monosulfide that features a low work function generates a space-charged region across the junction interface, and causes dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
51
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 139 publications
(61 citation statements)
references
References 39 publications
0
51
0
1
Order By: Relevance
“…Among the many factors affecting the activity, selectivity, and stability of heterogeneous catalysts, the adsorption behavior of reactants/ intermediates/products at the active sites of the catalyst surface plays a very important role. [26][27][28][29][30][31] The unique advantage of HEAs is that there are many kinds of metal sites in nanoparticles (NPs), and the main explanation for the ultrahigh activity and stability of HEA electrocatalysts is the synergistic effect of multiple metal sites. 32,33 The coexistence of multiple competing adsorption sites often leads to unsatisfactory reaction selectivity.…”
Section: Introductionmentioning
confidence: 99%
“…Among the many factors affecting the activity, selectivity, and stability of heterogeneous catalysts, the adsorption behavior of reactants/ intermediates/products at the active sites of the catalyst surface plays a very important role. [26][27][28][29][30][31] The unique advantage of HEAs is that there are many kinds of metal sites in nanoparticles (NPs), and the main explanation for the ultrahigh activity and stability of HEA electrocatalysts is the synergistic effect of multiple metal sites. 32,33 The coexistence of multiple competing adsorption sites often leads to unsatisfactory reaction selectivity.…”
Section: Introductionmentioning
confidence: 99%
“…The introduction of Ptn crowded the α-MoC surface thus contributed to eliminating excess surface oxygen species and further improved its stability. Besides, they found the unique CO activation and successive reforming pathway ( 13 C 16 O *' + *' → 13 C *' + 16 O *' , 2 13 C *' + 2 18 OH *' → 2 13 C 18 O + H2 + 2 * + 2 *' , 13 C *' + 2 18 OH *' → 13 C 18 O2 + H2 + 2 * + 2 *' ) to produce additional hydrogen by transient kinetic analysis using 13 C 16 O and H2 18 O as feeds (Fig. 9d).…”
Section: Water-gas Shift Reactionmentioning
confidence: 99%
“…However, different from the early development stage of SACs, it becomes harder for researchers to elevate the catalytic performance of SACs through aimless trials. In order to move further, researchers start to focus on the synergetic catalysts (like dual-atom site catalysts [8][9][10][11][12][13] , single atoms plus NPs 14 ), physical picture 15,16 and the electronic properties of the catalysts 17,18 . Among these, the underlying electronic states of active sites (i.e., supported single metal atoms) need to be comprehensively investigated because they are the direct adsorption sites for reactants and intermediates, the subtle change in microenvironment of which could exert an influence on the internal reactivity 16,19 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pt is widely accepted as the most effective polycrystalline single metal for catalyzing the ORR; however, the scarce resource and the resulting high price have severely hindered its large-scale application in LTFCs. , Fortunately, Pd shows an ORR electrocatalytic activity comparable with that of Pt in alkaline media and also has a much higher abundance in the Earth’s crust, , which make it a promising alternative. Moreover, plenty of studies have demonstrated that Pd is much more active for the electro-oxidation of alcohols than Pt in alkaline media. , Thus, Pd-based nanomaterials have become a very appealing material platform for designing and preparing high-performance electrocatalysts used for alkaline DAFCs.…”
Section: Introductionmentioning
confidence: 99%